Uncovering a tripartite relationship between patient, eHealth and healthcare professionals - Ladan, Muhammad Awwal; Wharrad, Heather; Windle, Richard (2018)
Background: Patients preferences have recently been identified as important factors in clinical practice. However, there is little information on how patient eHealth preferences influence healthcare professionals’ (HCPs) choices to use technology in their clinical practice especially in Sub-Saharan Africa (SSA). Aim: This is part of a study which explored factors influencing eHealth adoption and use among healthcare professionals in SSA. This section of the study aimed to uncover how patient preferences influence HCPs decisions on eHealth for clinical practice. Method: A mixed-method approach was adopted using Q-methodology. The viewpoints of thirty-six HCPs were explored in relation to eHealth adoption in their clinical practice. Each participant rank-ordered forty-six statements in relation to how they agreed or disagreed with them in their own clinical practice. This was followed by an interview to explore the reasons for their individual rankings. Results: Four viewpoints emerged showing how HCPs consider patient preferences when making decisions to use eHealth in their clinical practice. Conclusion: Findings suggest divergent viewpoints in relation to the role patient preferences play HCPs eHealth adoption in their clinical practices. These viewpoints could be seen as a tripartite relationship identifying how important patient eHealth preference influence HCP clinical choices.